PENGARUH KUALITAS PELAYANAN DAN SEGMENTASI PASAR TERHADAP TARGET PENJUALAN PT. HORASINDO WISATANUSA - Alvin Alvin; Thomas Sumarsan Goh; Nur Subiantoro (STIE-PMCI, 2021)
PT. Horasindo Wisatanusa is a company engaged in tour and travel services. There was a decline in service sales from 2015 to 2019 which was allegedly due to service quality factors and market segmentation that occurred in the company. The quality of service at the company is not good because customers often complain that the company is often late in informing changes to the tour schedule, there are additional costs that are not explained in the tour promotion package, customers often have difficulty contacting the company quickly because they only have one telephone line, and other facilities. promised is often different. The application of market segmentation in the company is not optimal because the company only focuses on customers who come from the city of Medan and has not expanded its market segmentation outside the city of Medan and the company has not collaborated with government agencies, campuses/universities, and hotel companies in recruiting more customers who take advantage of the services tours and travel provided by the company. The formulation of the problem in this study is whether there is an effect of Service Quality and Market Segmentation on Sales Targets at PT. Horasindo Wisatanusa. The method used in this research is a survey approach, the type of this research is descriptive quantitative and the nature of this research is descriptive explanatory. The population in this study were customers who used the company's tour and travel services from June 2020 to December 2020 as many as 80 respondents. The sampling technique in this study used simple random sampling and totaled 80 respondents. The data collection method was carried out using a Likert scale. The data analysis model used to answer the hypothesis is multiple regression. Â The results showed that partially and simultaneously Service Quality and Market Segmentation had a positive and significant effect on Sales Targets at PT. Horasindo Wisatanusa. Â Keywords : Service Quality, Market Segmentation, Sales Target.